化简下列各题.化简(1)(-2a) ³ b ⁴÷12a ³b²(2)x - 1

1个回答

  • (1)(-2a) ³ b ⁴÷12a ³b²

    =-8a³b ⁴÷12a ³b²

    =-2/3b²

    (2)x - 1/x÷(x - 1/x)

    =x-1/(x²-1)

    =(x³-x-1)/(x²-1)

    (3)x-y/x+2y ÷ x²-y²/x²+4xy+4y² -2, x=2-√2 ,y=2√2-1

    =(x-y)/(x+2y)×(x+2y)²/(x-y)(x+y)

    =(x+2y)/(x+y)

    =(2-√2+4√2-2)/(2-√2+2√2-1)

    =3√2/(√2+1)

    =3√2(√2-1)

    =6-3√2

    (4)2-x/x-1÷(x+1 - 3/x-1)

    =(2-x)/(x-1) ÷(x²-4)/(x-1)

    =(2-x)/(x-2)(x+2)

    =-1/(x+2)

    (5)x-2/x+2 - x+2/x-2,x=√2

    =(x²-4x+4-x²-4x-4)/(x+2)(x-2)

    =(-8x)/(x²-4)

    =-8√2/(2-4)

    =4√2

    (6)1/a+1 - a+3/a² -1 乘 a² -2a+1/a² +4a+3 ,a满足a² +2a-1=0

    =1/a+1 -(a+3)/(a+1)(a-1) ·(a-1)²/(a+1)(a+3)

    =1/(a+1) -(a-1)/(a+1)²

    =(a+1-a+1)/(a+1)²

    =2/(a²+2a+1)

    =2/(1+1)

    =1

    (7)1 - x-y/x+2y ÷ x²-y²/x²+4xy+4y² ,x=√2,y=1

    =1-(x-y)/(x+2y)×(x+2y)²/(x+y)(x-y)

    =1- (x+2y)/(x+y)

    =(x+y-x-2y)/(x+y)

    =-y/(x+y)

    =-1/(√2+1)

    =-(√2-1)

    =-√2+1